Taking sides Clashing views in science, technology, and society - Easton, Thomas A. (Boston McGraw-Hill Higher Education, 2009)
UNIT 1. The place of science and technology in society -- Does politics come before science in current government decision making? -- Should government restrict the publication of unclassified but "sensitive" research? -- Should the Internet be neutral? -- UNIT 2. The environment -- Should society act now to halt global warming? -- Is it time to revive nuclear power? -- Will hydrogen replace fossil fuels for cars? -- UNIT 3. Human health and welfare -- Do falling birth rates pose a threat to human welfare? -- Is there sufficient scientific research to conclude that cell phones cause cancer? -- Should DDT be banned worldwide? -- Should potential risks slow the development of nanotechnology? -- Are genetically modified foods safe to eat? -- UNIT 4. Space -- Should we expand efforts to find near-earth objects? -- Will the search for extraterrestrial life ever succeed? -- Is "manned space travel" a delusion? -- UNIT 5. The computer revolution -- Does the Internet strengthen social connections? -- Does the spread of surveillance technology threaten privacy? -- Should the world’s libraries be digitized? -- UNIT 6. Ethics -- Is the use of animals in research justified? -- Is it ethically permissible to clone human cells? -- Is wind power green? -- Are "space sunshades" a possible answer to global warming?
Includes bibliographical references and index.
Keywords: Science -- Social aspects; Technology -- Social aspects; Khoa học; Công nghệ; Xã hội